Pengaruh pemberian jus kurma (Dactilifera phoenix) pada ibu bersalin kala I terhadap durasi persalinan di wilayah kerja Puskesmas Langsa Baro - Cut Mutiah (Jurnal SAGO Gizi dan Kesehatan, 2019)
Background: Labor is a physiological process experienced by women through a series of natural processes starting from uterine contractions to be able to give birth to the fetus. Research shows that during normal delivery mothers are still allowed to eat and drink because there is no strong evidence that causes aspiration. Nutrition during labor as an energy source can be obtained from dates (Phoenix Dactilifera). Research shows dates have good nutritional value for carbohydrate-rich bodies and have been shown to influence the progress of labor and increase labor, and reduce postpartum hemorrhage.Objective: to prove whether there is an effect of the administration of date palm juice (Dactilifera Phoenix) to first-time mothers on the duration of labor in the Langsa Baro Health Center.Method: This research is a quasi experiment with a nonequivalent posttest only control group design approach. This research was conducted in the Work Area of the Langsa Baro Health Center from July 11 to September 22 2017 with the place of delivery in the Polindes. The number of samples for each group was 15 people in the intervention group and 15 people in the control group. To avoid drop outs, the number of samples is added by 10% (2 people) so that each group is 17 people. Data analysis Data normality test uses the Shapiro-Wilk test and Parametric Test uses the Independent T-Test for normal distribution data to look for differences in the average of the control group with treatment.Results: The results of the study with the data normality test with the Shapiro-Wilk test showed that the duration of labor in the two groups had a p-value of 0.247 (p> 0.05) meaning that the data were normally distributed. And the Independent T-Test shows the difference in the average duration of labor in the two groups. In the control group the average duration of labor was 12.09 while in the treatment group it was 11.23, showing no significant difference in the mean values in the two groups with p-value = 0.011. This shows that statistically the administration of date palm juice cannot accelerate the duration of labor.Conclusion: There were differences in the average duration of labor in the control and treatment groups. In the control group the average duration of labor was 12.09 hours and the treatment group was 11.23 hours. And the date palm juice did not significantly speed up the duration of labor (p-value = 0.011).